Relation Between Change in Renal Function and Cardiovascular Outcomes in Atorvastatin-Treated Patients (from the Treating to New Targets [TNT] Study) - Shepherd, James; Breazna, Andrei; Deedwania, Prakash C.; LaRosa, John C.; Wenger, Nanette K.; Messig, Michael; Wilson, Daniel J. (The American journal of cardiology, 2016)
Statins may have nephroprotective as well as cardioprotective effects in patients with cardiovascular disease. In the Treating to New Targets (TNT) study (NCT00327691), patients with coronary heart disease (CHD) were randomized to atorvastatin 10 or 80 mg/day and followed for 4.9 years. The relation between intrastudy change in estimated glomerular filtration rate (eGFR) from baseline and the risk of major cardiovascular events (MCVEs, defined as CHD death, nonfatal non–procedure-related myocardial infarction, resuscitated cardiac arrest, or fatal or nonfatal stroke) was assessed among 9,500 patients stratified by renal function: improving (change in eGFR more than +2 ml/min/1.73 m2), stable (−2 to +2 ml/min/1.73 m2), and worsening (less than −2 ml/min/1.73 m2). Compared with patients with worsening renal function (1,479 patients, 15.6%), the rate of MCVEs was 28% lower in patients with stable renal function (2,241 patients, 23.6%) (hazard ratio [HR] 0.72; 95% confidence interval [CI] 0.60 to 0.87; p = 0.0005) and 64% lower in patients with improving renal function (5,780 patients, 60.8%; HR 0.36; 95% CI 0.30 to 0.43; p <0.0001). For each 1 ml/min/1.73 m2 increase in eGFR, the absolute reduction in the rate of MCVEs was 2.7% (HR 0.973; 95% CI 0.967 to 0.980; p <0.0001). An absolute MCVE rate reduction per 1 ml/min/1.73 m2 increase in eGFR of 2.0% was reported with atorvastatin 10 mg and 3.3% with atorvastatin 80 mg. In conclusion, intrastudy stabilization or increase in eGFR in atorvastatin-treated patients with CHD from the TNT study was associated with a reduced rate of MCVEs. Statin-treated CHD patients with progressive renal impairment are at high risk for future cardiovascular events.